Law Enforcement Activity of the National Guard of Ukraine on Ensuring Public Security and Order: Problems and Ways of Their Solution - K. O. Chyshko (Law and Safety)
The author has studied the content of normative and legal acts regulating public relations in the field of ensuring public security and order by the National Guard of Ukraine (NGU). The author has paid direct attention to theoretical bases of the concept of “public security” and “public order”. Relevant problems of ensuring public security and order by the NGU have been described; specific ways of eliminating legal and organizational problems of such provision have been suggested.